Idiopathic hirsutism and dyslipidemia: A systematic review, meta‐analysis, and meta‐regressions. (31st January 2023) - Amiri, Mina; Mahmoudieh, Leila; Sheidaei, Ali; Ramezani Tehrani, Fahimeh
Abstract: Background: Despite existing several kinds of studies on idiopathic hirsutism (IH) and its association with metabolic disturbances, a limited number of studies have assessed lipid profiles in patients with IH with conflicting and inconclusive results. This study aimed to evaluate the lipid profiles in women with IH, compared to those of polycystic ovary syndrome (PCOS) and healthy controls. Materials and Methods: For this systematic review and meta‐analysis, PubMed, Scopus, and EMBASE databases were searched to obtain studies published from inception to July 2021 investigating the lipid parameters, including triglyceride (TG), total cholesterol (TC), low‐density lipoprotein cholesterol (LDL‐C), and high‐density lipoprotein cholesterol (HDL‐C) in women with IH, compared to control groups. A meta‐regression and subgroup analysis were conducted to explore heterogeneity sources. Publication bias was assessed by the Egger test. Results: Of 209 studies retrieved through searching databases and other sources, a total of 12 studies including 3913 participants were included for the meta‐analysis. This meta‐analysis showed higher standardized mean difference (SMD) of TC (SMD: 0.09 mg/dl; 95% CI: 0.001, 0.18) and lower SMD of HDL‐C (SMD: −0.10 mg/dl; 95% CI: −0.18, −0.02) in women with IH, compared to those of the healthy controls, whereas there were no significant differences in the SMDs of TG and LDL‐C between the study groups. This study also revealed no difference in the levels of lipid profiles of women with IH in comparison with PCOS patients, except for TG (SMD: −0.24 mg/dl; 95% CI: −0.46, −0.02). The results of subgroup analysis based on the study design revealed no significant differences in the SMD of lipid parameters between women with IH and healthy controls. We also found no significant difference in the levels of lipid profiles of women with IH versus PCOS patients, except for HDL‐C in the subgroup of case–control studies (SMD: 0.18 mg/dl; 95% CI: 0.01, 0.34). Conclusion: This study demonstrated that the majority of lipid parameters were not significantly different in women with IH, compared to those of healthy and PCOS controls.